Safeguarding public service interpreting in times of crises: Limitations and possibilities of lower-level testing and training - Lian, Marius; Vaage, Mari Nielsen; Roth, Lisa Inger (International Journal of Language, Translation and Intercultural Communication, 2025)
Interpreters are crucial for accessing public services and participating in democratic and legal processes. In Norway, interpreting is regulated by the Interpreting Act, which mandates formal qualifications for listing in the National Registry of Interpreters. Oslo Metropolitan University leads in public service interpreting (PSI) education, offering schemes like the Bilingual Proficiency Test and an introductory course. This scheme, available in around 80 languages, provides basic language testing and limited training, qualifying candidates for the national register's lowest level. The paper examines whether basic language testing and limited training is sufficient for the demands of public sector interpreting. It presents the legal framework for interpreting in Norway, the role of Oslo Metropolitan University in interpreter qualification, and the flexibility of the Bilingual Proficiency Test, particularly its rapid response to the influx of Ukrainian refugees. The paper concludes by evaluating the limitations and potentials of lower-level qualification schemes in PSI.